2020
DOI: 10.1155/2020/9259017
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Use of Standardized Outcome Measures for Stroke Rehabilitation among Physiotherapists in Ghana

Abstract: Background. The use of standardized outcome measures is an aspect of good clinical practice and essential to the rehabilitation of patients suffering from stroke. Literature reports regarding the extent of usage of outcome measures in stroke rehabilitation by physiotherapists globally are inconsistent. In addition, the patronage of outcome measures in stroke rehabilitation in low-resourced countries is uncertain. Objective. This study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 15 publications
3
16
1
Order By: Relevance
“…Previous systematic reviews have identified multiple measures of sitting balance used for people after stroke ( 90 ), with over 60 different measures of standing balance in the adult population ( 69 ), and over 30 measures of mobility for older adults ( 91 ). We found that the assessment tools included in at least 70% of CPGs (i.e., BBS, 6MWT, TUG, and 10mWT) are consistent with the tools most frequently used in clinical practice as indicated by clinician surveys conducted in Canada ( 92 – 94 ), Colombia ( 95 ), Ghana ( 27 ), and Germany ( 32 ). Moreover, our analyses considering CPGs by country income level showed that the BBS, 6MWT, TUG, and 10mWT, are currently recommended by CPGs from middle- and high-income countries.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previous systematic reviews have identified multiple measures of sitting balance used for people after stroke ( 90 ), with over 60 different measures of standing balance in the adult population ( 69 ), and over 30 measures of mobility for older adults ( 91 ). We found that the assessment tools included in at least 70% of CPGs (i.e., BBS, 6MWT, TUG, and 10mWT) are consistent with the tools most frequently used in clinical practice as indicated by clinician surveys conducted in Canada ( 92 – 94 ), Colombia ( 95 ), Ghana ( 27 ), and Germany ( 32 ). Moreover, our analyses considering CPGs by country income level showed that the BBS, 6MWT, TUG, and 10mWT, are currently recommended by CPGs from middle- and high-income countries.…”
Section: Discussionsupporting
confidence: 67%
“…The use of standardized assessment tools in physical therapy practice is inconsistent ( 27 – 32 ). Common barriers to the use of standardized assessment tools are lack of time, insufficient knowledge, lack of description of how to administer standardized assessment tools, and low perceived value of some instruments ( 24 , 28 , 29 , 31 – 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…The rest (36.8%) used them occasionally or rarely. In Ghana, Agyenkwa et al ( 2020 ) also showed that 21% of physiotherapists working in stroke care used standardised outcome measures all the time (5/5 patients) and 21% often (3-4/5 patients) (Agyenkwa et al 2020 ). Our results are similar to those of Demers et al ( 2019 ) who compared the use of outcome measures between India and Canada.…”
Section: Discussionmentioning
confidence: 99%
“…However, later in 2019, Odole et al ( 2019 ) reported contrasting results with a 68% use of knee osteoarthritis outcome measures among Nigerian physiotherapists (Odole et al 2019 ). Agyenkwa et al ( 2020 ) found that Ghanaian physiotherapists (47.6%) had low use of standardised outcome measures (Agyenkwa et al 2020 ). One study from Nigeria dealt with harvesting perceived barriers and facilitators to the use of outcome measures (Obembe et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These few studies revealed that the standardised assessments of somatosensation are underutilised. Evidence regarding the use of validated and reliable instruments by therapists in stroke rehabilitation varies across countries [48][49][50][51]. For example, the use of standardised assessments was notably high in the United Kingdom but relatively low in Canada, likely due to lack of time and knowledge about outcome measures.…”
Section: Discussionmentioning
confidence: 99%